An extension to the CAM16 colour appearance model to predict the size effect. Issue 4 (18th January 2021) - Gao, Cheng; Li, Changjun; Xiao, Kaida; Luo, Ming Ronnier; Pointer, Michael R.
Abstract: Experience and experimental results show that the perceived colour appearance of an object varies with the size of that object or the viewing angle. Based on available visual size‐effect data, it is found that the size effect can be compensated in the CAT16 cone‐like space. Furthermore, it is found that, similar to the von Kries chromatic adaptation, size‐effect correction can be operated independently on the different cone channels. Hence, the size effect can be easily built into the CAM16 model to predict the colour appearance for stimuli of varying sizes.